Gambaran Pelaksanaan Keselamatan dan Kesehatan Kerja Pada Sektor Konstruksi Pembangunan Gedung Grand Classic Hotel Cikarang di PT Wijaya Kusuma Contractors - Setiawan Laia; Evi Vestabilivy (STIKes Persada Husada Indonesia, 2017)
Occupational safety and health is a thought and effort to prevent accidents. This study aims to find out the Implementation of Occupational Safety and Health in the Construction Sector Construction of Grand Classic Hotel Cikarang Building in PT. WijayaKusuma Contractors. This research uses qualitative method with phenomology approach. Selection of informants using Puposive Sampling technique. The focus of this research are: Age, Workload, Working Capacity, Physical Factor, Chemical Factor, and Biological Factor. With data collection techniques using in-depth interviews, documentation, and observation. From the result of the research, it can be seen that the implementation of K3 in the Construction Sector of Grand Classic Hotel Cikarang Building in PT.WijayaKusuma Contractors has been running maximally in accordance with the standard regulations of ISO 14001, SMK3 and OHSAS. But there are still some shortcomings in this implementation because there are still some workers who are not aware of K3, such as not complying with existing regulations and can potentially lead to work accidents.